Can assimilating snow monitoring information offset the adverse effects of precipitation data scarcity in hydrological modelling applications? - Abbasnezhadi, Kian; Rousseau, Alain N. (2020)
The applicability of the Canadian Precipitation Analysis products known as the Regional Deterministic Precipitation Analysis (CaPA-RDPA) for hydrological modelling in boreal watersheds in Canada, which are constrained with shortage of precipitation information, has been the subject of a number of recent studies. The northern and mid-cordilleran alpine, sub-alpine, and boreal watersheds in Yukon, Canada, are prime examples of such Nordic regions where any hydrological modelling application is greatly scrambled due to lack of accurate precipitation information. In the course of the past few years, proper advancements were tailored to resolve these challenges and a forecasting system was designed at the operational level for short- to medium-range flow and inflow forecasting in major watersheds of interest to Yukon Energy. This forecasting system merges the precipitation products from the North American Ensemble forecasting System (NAEFS) and recorded flows or reconstructed reservoir inflows into the HYDROTEL distributed hydrological model, using the Ensemble Kalman Filtering (EnKF) data assimilation technique. In order to alleviate the adverse effects of scarce precipitation information, the forecasting system also enjoys a snow data assimilation routine in which simulated snowpack water content is updated through a distributed snow correction scheme. Together, both data assimilation schemes offer the system with a framework to accurately estimate flow magnitudes. This robust system not only mitigates the adverse effects of meteorological data constrains in Yukon, but also offers an opportunity to investigate the hydrological footprint of CaPA-RDPA products in Yukon, which is exactly the motivation behind this presentation. However, our overall goal is much more comprehensive as we are trying to elucidate whether assimilating snow monitoring information in a distributed hydrological model could meet the flow estimation accuracy in sparsely gauged basins to the same extent that would be achieved through either (i) the application of precipitation analysis products, or (ii) expanding the meteorological network. A proper answer to this question would provide us with valuable information with respect to the robustness of the snow data assimilation routine in HYDROTEL and the intrinsic added-value of using CaPA-RDPA products in sparsely gauged basins of Yukon.
Keywords: Rousseau_Alain

Quantitative assessment on basin-scale hydrological services of wetlands - Wu, Yanfeng; Zhang, Guangxin; Rousseau, Alain N. (Science China Earth Sciences, 2020)

Deriving synthetic rating curves from a digital elevation model to delineate the inundated areas of small watersheds - Gordon, Camila A.; Foulon, Etienne; Rousseau, Alain N. (Journal of Hydrology: Regional Studies, 2023)
Keywords: Infolettre; Infolettre_Janvier_2024; Rousseau_Alain

Are spatial distribution and aggregation of wetlands reliable indicators of stream flow mitigation? - Blanchette, Marianne; Rousseau, Alain N.; Savary, Stéphane; Foulon, Étienne (Journal of Hydrology, 2022)
Keywords: Rousseau_Alain

Extension of a Monolayer Energy-Budget Degree-Day Model to a Multilayer One - Augas, Julien; Foulon, Etienne; Rousseau, Alain N.; Baraër, Michel (Water, 2024)
This paper presents the extension of the monolayer snow model of a semi-distributed hydrological model (HYDROTEL) to a multilayer model that considers snow to be a combination of ice and air, while accounting for freezing rain. For two stations in Yukon and one station in northern Quebec, Canada, the multilayer model achieves high performances during calibration periods yet similar to the those of the monolayer model, with KGEs of up to 0.9. However, it increases the KGE values by up to 0.2 during the validation periods. The multilayer model provides more accurate estimations of maximum SWE and total spring snowmelt dates. This is due to its increased sensitivity to thermal atmospheric conditions. Although the multilayer model improves the estimation of snow heights overall, it exhibits excessive snow densities during spring snowmelt. Future research should aim to refine the representation of snow densities to enhance the accuracy of the multilayer model. Nevertheless, this model has the potential to improve the simulation of spring snowmelt, addressing a common limitation of the monolayer model.
Keywords: Baraer_Michel; Rousseau_Alain

What is the Trade-Off between Snowpack Stratification and Simulated Snow Water Equivalent in a Physically-Based Snow Model? - Augas, Julien; Abbasnezhadi, Kian; Rousseau, Alain N.; Baraer, Michel (Water, 2020)
In Nordic watersheds, estimation of the dynamics of snow water equivalent (SWE) represents a major step toward a satisfactory modeling of the annual hydrograph. For a multilayer, physically-based snow model like MASiN (Modèle Autonome de Simulation de la Neige), the number of modeled snow layers can affect the accuracy of the simulated SWE. The objective of this study was to identify the maximum number of snow layers (MNSL) that would define the trade-off between snowpack stratification and SWE modeling accuracy. Results indicated that decreasing the MNSL reduced the SWE modeling accuracy since the thermal energy balance and the mass balance were less accurately resolved by the model. Nevertheless, from a performance standpoint, SWE modeling can be accurate enough with a MNSL of two (2), with a substantial performance drop for a MNSL value of around nine (9). Additionally, the linear correlation between the values of the calibrated parameters and the MNSL indicated that reducing the latter in MASiN increased the fresh snow density and the settlement coefficient, while the maximum radiation coefficient decreased. In this case, MASiN favored the melting process, and thus the homogenization of snow layers occurred from the top layers of the snowpack in the modeling algorithm.
Keywords: Baraer_Michel; Rousseau_Alain

Quantifying streamflow regulation services of wetlands with an emphasis on quickflow and baseflow responses in the Upper Nenjiang River Basin, Northeast China - Wu, Yanfeng; Zhang, Guangxin; Rousseau, Alain N.; Xu, Y. Jun (Journal of Hydrology, 2020)
Keywords: Rousseau_Alain

Wetland-based solutions against extreme flood and severe drought: Efficiency evaluation of risk mitigation - Wu, Yanfeng; Sun, Jingxuan; Hu, Boting; Zhang, Guangxin; Rousseau, Alain N. (Climate Risk Management, 2023)
Keywords: Infolettre; Infolettre_Juin_2023; Rousseau_Alain

Quantifying the mitigation effect of natural landscapes during an extraordinary flood: the prominent role of the Otter Creek wetlands to middlebury, Vermont, USA, during Tropical Storm Irene - Lachapelle, Simon; Rousseau, Alain N.; Blanchette, Marianne; Foulon, Etienne; Savary, Stéphane (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2025)
Keywords: Infolettre; Infolettre_Avril_2025

Setting Targets for Wetland Restoration to Mitigate Climate Change Effects on Watershed Hydrology - Goyette, Jean-Olivier; Savary, Stéphane; Blanchette, Marianne; Rousseau, Alain N.; Pellerin, Stéphanie; Poulin, Monique (Environmental Management, 2023)
Keywords: Infolettre; Infolettre_Fevrier_2023; Rousseau_Alain

Can the combining of wetlands with reservoir operation reduce the risk of future floods and droughts? - Wu, Yanfeng; Sun, Jingxuan; Hu, Boting; Xu, Y. Jun; Rousseau, Alain N.; Zhang, Guangxin (Hydrology and Earth System Sciences, 2023)
Wetlands and reservoirs are important water flow and storage regulators in a river basin; therefore, they can play a crucial role in mitigating flood and hydrological drought risks. Despite the advancement of river basin theory and modeling, our knowledge is still limited about the extent to which these two regulators could perform such a role, especially under future climate extremes. To improve our understanding, we first coupled wetlands and reservoir operations into a semi-spatially explicit hydrological model and then applied it in a case study involving a large river basin in northeast China. The projection of future floods and hydrological droughts was performed using the hydrological model during different periods (near future: 2026–2050, middle century: 2051–2075, and end century: 2076–2100) under five future climate change scenarios. We found that the risk of future floods and hydrological droughts can vary across different periods – in particular, it will experience relatively large increases and slight decreases. This large river basin will experience flood events of longer duration, with larger peak flows and volume, and of enhanced flashiness compared to the historical period. Simultaneously, the hydrological droughts will be much more frequent, with longer durations and more serious deficits. Therefore, the risk of floods and droughts will, overall, increase further under future climate change even under the combined influence of reservoirs and wetlands. These findings highlight the hydrological regulation function of wetlands and reservoirs and attest that the combining of wetlands with reservoir operation cannot fully eliminate the increasing future flood and drought risks. To improve a river basin's resilience to the risks of future climate change, we argue that the implementation of wetland restoration and the development of accurate forecasting systems for effective reservoir operation are of great importance. Furthermore, this study demonstrated a wetland–reservoir integrated modeling and assessment framework that is conducive to risk assessment of floods and hydrological droughts and that can be used for other river basins in the world.
Publisher: Copernicus GmbH
Keywords: Infolettre; Infolettre_Septembre_2023; Rousseau_Alain

Impacts of high precipitation on the energy and water budgets of a humid boreal forest - Isabelle, Pierre-Erik; Nadeau, Daniel F.; Anctil, François; Rousseau, Alain N.; Jutras, Sylvain; Music, Biljana (Agricultural and Forest Meteorology, 2020)
Keywords: Ouvrage_Collectif_Numéro1; Rousseau_Alain

Wetland mitigation functions on hydrological droughts: From drought characteristics to propagation of meteorological droughts to hydrological droughts - Wu, Yanfeng; Sun, Jingxuan; Blanchette, Marianne; Rousseau, Alain N.; Xu, Y. Jun; Hu, Boting; Zhang, Guangxin (Journal of Hydrology, 2023)
Keywords: Rousseau_Alain

Using the ecosystem serviceshed concept in conservation planning for more equitable outcomes - Goyette, Jean-Olivier; Mendes, Poliana; Cimon-Morin, Jérôme; Dupras, Jérôme; Pellerin, Stéphanie; Rousseau, Alain N.; Poulin, Monique (Ecosystem Services, 2024)
Keywords: Infolettre; Infolettre_Avril_2024

Machine Learning vs. Physics-Based Modeling for Real-Time Irrigation Management - Gumiere, Silvio J.; Camporese, Matteo; Botto, Anna; Lafond, Jonathan A.; Paniconi, Claudio; Gallichand, Jacques; Rousseau, Alain N. (Frontiers in Water, 2020)
Keywords: Rousseau_Alain

Quantitative assessment of hydrological multifunctionality of headwater wetlands - Wu, Yanfeng; Ni, Bingbo; Xue, Zhenshan; Dong, Liqin; Zhang, Kun; Rousseau, Alain N.; Zhang, Guangxin; Song, Kaishan (Journal of Hydrology, 2025)
Keywords: Infolettre; Infolettre_Avril_2025

A dual isotopic framework for identifying nitrate sources in surface runoff in a small agricultural watershed, northeast China - Sui, Yuanyuan; Ou, Yang; Yan, Baixing; Rousseau, Alain N.; Fang, Yunting; Geng, Runzhe; Wang, Lixia; Ye, Nan (Journal of Cleaner Production, 2020)
Keywords: Rousseau_Alain

Does the Operation of a Reservoir Alter Its Interactions with the Atmosphere? Investigating the Role of Advective Fluxes on Energy and Hydrological Balances of the Romaine-2 Subarctic Hydropower Reservoir - Pierre, Adrien; Nadeau, Daniel F.; Thiboult, Antoine; Rousseau, Alain N.; Anctil, François; Deblois, Charles P.; Demarty, Maud; Isabelle, Pierre-Erik; Tremblay, Alain (Journal of Hydrometeorology, 2024)
Abstract The hydrological processes of cascading hydroelectric reservoirs differ from those of lakes, due to the importance of the inflows and outflows that vary with energy demand. These heat and water advection terms are rarely considered in water body energy balance analyses even though reservoirs are common man-made structures, especially in North America, and thus may affect the regional climate. This study provides a comprehensive assessment of the water and energy balance of the 85-km 2 Romaine-2 northern reservoir (50.69°N, 63.24°W), mean depth of 44 m, highlighting the significant contribution of the advection heat fluxes. The water balance input was primarily controlled by upstream (turbine) inflows (77.6%), while lateral (natural) inflows and direct precipitation represented 21.2% and 1.2%, respectively. As for the reservoir’s heat budget, the net advection of heat accounted on average for 25.0% of the input, of which net radiation was the largest component (73.3%). After accounting for the absence of energy balance closure, latent heat and sensible heat fluxes represented 73.2% and 25.1% of total energy output from the reservoir, respectively. The thermal regime was influenced by the hydrological flow conditions, which were regulated by reservoir management. This played a major role in the evolution of the thermocline and the temperature of the epilimnion, and ultimately, in the dynamics of the turbulent heat fluxes. This study suggests that the heat advection term represents a large fraction of the heat budget of northern reservoirs and should be properly considered.